Susceptibility and multidrug resistance of Arcobacter isolates within the Czech Republic - Šilha, David; Šilhová, Lucie (Vilnius University, 2016)
Arcobacter spp. is Gram-negative, slender, spiral-shaped rods and belong to the family Campylobacteraceae. Many of these species have been isolated especially from poultry, meat, faeces, and from aborted cattle foetuses. Major route of Arcobacter transmission to human is consumption of contaminated foods of animal origin as well as non-treated water drinking . Resistance to commonly used antibiotics observed among Arcobacter spp. emphasises the importance of research in this area. The aim of this study was to evaluate the antimicrobial susceptibility of A. butzleri and A. cryaerophilus isolated from meat poultry, waste water and human faeces within the Czech Republic.
Citlivost a multirezistence isolátů Arcobacter spp. v rámci České republiky
Keywords: Arcobacter spp.; antibiotics; resistence; pathogen; Arcobacter spp.; antibiotika; rezistence; patogen